RESPONSE OF LOWLAND RICE NSIC RC308 (ORYZA SATIVA L.) TO APPLICATION OF COMMERCIAL ORGANIC AND INORGANIC FERTILIZERS - Mejia, Junriel John P.; Bañoc, Dionesio M. (Journal of Agriculture and Technology Management, 2019)
The study evaluated the effects of combined application of commercial organic and inorganic fertilizers on the growth and yield performance of lowland rice NSIC Rc308, determine the appropriate level of application and evaluate its profitability by using different levels of organic and inorganic fertilizers. The experimental plots were laid out in a Randomized Complete Block Design (RCBD) with three replications and six treatments as follows: T 0 = No fertilizer application (control), T 1 = 120-60-60 kg ha -1 N, P 2 O 5 , K 2 O, T 2 = 10 bags ha -1 Plantmate Organic Fertilizer (POF) only, T 3 = 10 bags ha -1 POF + Prime Emulsifiable Concentrate (EC) 4 liters ha -1 , T 4 = 10 bags ha -1 POF + 60-30-30 kg ha -1 N, P 2 O 5 , K 2 O and T 5 = 5 bags ha -1 POF + 60-30-30 kg ha -1 N, P 2 O 5 , K 2 O. It was hypothesized that combined application of organic and inorganic fertilizers can improve rice productivity and increase income. Application of commercial organic and inorganic fertilizers significantly affected the number of nodal roots and grain yield than those unfertilized plants. However, inorganic fertilized plants significantly extended their heading and maturity period, taller plant height, high leaf area index (LAI), heavier straw, more nodal roots, heavier shoot dry weight and higher grain yield than unfertilized control.  Plants applied with ten bags ha -1 POF + 4 liters ha -1 Prime EC produced higher grain yield (3.03 tha -1 ) and net income of PhP 24,743.00 ha -1 . Therefore, combined application of POF + Prime EC is recommended for lowland rice production.